2020
DOI: 10.1021/acs.orglett.0c03081
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Radical Intermolecular Addition of Unbiased Alkenes to Aldehydes

Abstract: The intermolecular reductive radical coupling of aldehydes with non-activated alkenes, employing metal hydride atom transfer (MHAT) catalysis with a combination of Fe II and Fe III salts, is described. This constitutes the first use of aldehydes as viable acceptor groups in MHAT reactions. The insights gained in this study led to the reexamination of the previously reported intramolecular version of the reaction, and the addition of Fe II salts allowed the development of a more efficient second-generation appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…In the latter case, it was recently demonstrated that Fe-H based HAT reactivity on olefins is compatible with aldehyde electrophiles to generate branched dialkyl carbinol products. 18 Finally, numerous a-oxy alkyl radical precursors have been employed to achieve C-C bond formation. Thus, the use of O-heteroatom acetals containing S, 19 Se 20 and halogen atoms 21 have been employed in intermolecular couplings with olefins.…”
Section: Background and Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, it was recently demonstrated that Fe-H based HAT reactivity on olefins is compatible with aldehyde electrophiles to generate branched dialkyl carbinol products. 18 Finally, numerous a-oxy alkyl radical precursors have been employed to achieve C-C bond formation. Thus, the use of O-heteroatom acetals containing S, 19 Se 20 and halogen atoms 21 have been employed in intermolecular couplings with olefins.…”
Section: Background and Historical Contextmentioning
confidence: 99%
“…The TCNHPI-based RAEs were prepared from corresponding a-hydroxy acids using a onepot O-protection and acid activation protocol (see SI for details). Aside from simple alkyl chains (15−17), a broad range of functional groups could be tolerated, such as terminal alkenes(18), internal alkenes(39), alkyl halides (19, 21), acetals(20), acetates(22), silyl ethers(23), esters(25), ethers(26, 27), imides(31), nitriles (38), azides(37), carbamates (33), and heterocycles(28)(29)(30)32). The directing group on hydroxy group was not limited to Bz as Ac-and Piv-substituted analogues also worked well under the same conditions (34−36).…”
mentioning
confidence: 99%
“…The development of dehydrogenative imine additions of π-unsaturated pronucleophiles via hydrogen autotransfer of amine proelectrophiles (so-called “hydroaminoalkylations”) has largely focused on early transition metal catalysts . With only three exceptions, , corresponding late transition metal-catalyzed variants have required non-native directing groups. , Metal-catalyzed intermolecular reductive couplings of unactivated olefins with unactivated aldehydes using feedstock reductants have proven elusive, although promising strategies have emerged. , While intra- and intermolecular hydrogenative and transfer hydrogenative carbonyl reductive couplings of aryl halides have been accomplished, enantioselective variants, the use of alkyl halide pronucleophiles, and hydrogen autotransfer processes have not been described. Additionally, despite truly impressive progress on the reductive carboxylation of π-unsaturated reactants with CO 2 mediated by silane, , the use of inexpensive feedstock reductants in such processes has not been described (although photochemical promotion may unlock this challenge)…”
Section: Future Opportunities and Objectivesmentioning
confidence: 99%
“…The reaction proceeds under metal hydride atom transfer (MHAT) conditions in the presence of both Fe(II) and Fe(III) salts (Scheme 51). 79 Typically, these radical additions are challenging since they proceed through unstable alkoxyl radical intermediates that tend to revert back to the more stable carboncentered radical via β-fragmentation. The authors postulated that Fe(II) species could play a beneficial role in stabilizing the alkoxyl radical through the persistent radical effect, thereby preventing its potential rearrangement before the desired reaction takes place.…”
Section: ■ Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%